(untitled) (LEARNing Landscapes, 2018)
Re)telling and (re)living our stories within our response community, we became more wakeful (Greene, 1995) to processes of (re)naming that contoured ways in which we were storied in diverse worlds (Lugones, 1987). We also gained a deeper appreciation as to how we, in turn, (re)named ourselves and others. Narratively inquiring (Clandinin & Connelly, 2000) into the stories of our names, we autobiographically illuminate our understandings of our (shifting and multiple) selves and experiences and make visible educative possibilities for educators and others looking to compose spaces of mutual care and understanding within the many worlds we co-inhabit.